Virtual Grid Spatial Reusing Algorithm for MAC Address Assignment in Wireless Sensor Network. (2008) - Tian Tian, Ye Ye; Sheng Sheng, Min Min; Li Li, Jiandong Jiandong
Abstract : Compared with the small overhead of data payload in sensor networks, the overhead of MAC address is significant from the point of view of energy-saving. A distributed algorithm (Virtual Grid Spatial Reusing-VGSR) for MAC address assignment is presented in this paper, which is a low energy cost algorithm and reduces the size of the fixed MAC address largely based on the mapping of the geographical position. Moreover, VGSR algorithm scales well with the network size and achieves the optimum performance by adjusting the communication range of sensor nodes. In typical scenarios, the MAC address size is 5 bits and the corresponding average size is only 3.86 bits, which outperforms other existing approaches.